Differentiated Approach in Learning the Quran and Hadith at SDIT Plus AL-Muhsinin - Muhammad Ridho Abdul Rozaq; Wendi Saepul Mikdar; Muhammad Rakha Fauzan; Asep Nursobah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The purpose of this study is to examine the implementation of a differentiation approach in learning the Quran and Hadith at the elementary school level. This study uses a qualitative approach with a case study design. This approach was chosen because it is suitable for exploring in depth the application of differentiation-based learning of the Quran and Hadith at the elementary school level. The research location was SDIT Plus Al-Muhsinin. The application of a differentiation approach in learning the Quran and Hadith at the elementary school level is effective in accommodating the diverse needs and characteristics of students. Through the use of varied strategies that are responsive to students' cognitive, affective, and psychomotor aspects, teachers are able to provide a more meaningful learning experience and are in accordance with psychopedagogical principles.